BPOM Supervision in Increasing Consumer Protection for Online Sales of "Brilliant Philippines "Brand Skin Care Products" - Ayu Andira; Danang Wahyu Muhammad (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
BPOM stated that Skincaree Brilliant Philippines products are unsafe because they are thought to contain retinoic acid and hydroquinone ingredients that can damage the skin. This is the basis for BPOM withdrawing the permit and prohibiting its distribution. The formulation of the problem in this research first examines how the role and function of BPOM in the distribution of Skincare Brilliant Philippines. Second, what is the legal protection for consumers against the distribution of illegal cosmetics online? The research method used is empirical law with a qualitative descriptive approach, compiling various literary sources, including primary and secondary data. Based on an extended analysis, researchers saw that the Skincare Beerliant Philippines product is not safe from which to experience the benefits. Furthermore, BPOM has played an essential role in the supervision of cosmetics because it has carried out a series of tasks, functions, and functions of BPOM related to the supervision of cosmetics. The results of the research found that BPOM should have strict supervision by Presidential Decree Number 80 of 2017 concerning the Food and Drug Monitoring Agency, Law no. 80 of 2017 concerning BPOM Article (1) paragraph (1) and Republic of Indonesia Health Minister Regulation No. 1175/MEeNKEeS/PEeR/VIII/2010 concerning Cosmetics Production Permits which regulate consumer protection against illegal products and distribution permits so that the public feels protected and don't worry about mass-marketed products.